Stabilization of dextransucrase from Leuconostoc mesenteroides NRRL B-640 - Purama, Ravi Kiran (Springer India, 2010)
Stabilization of dextransucrase from Leuconostoc mesenteroides NRRL B-640 with various stabilizers at different temperatures was studied. Dextransucrase was stable at lower temperatures (10–30°C) and lost the activity at above 30°C. The salts such as CaCl(2), CoCl(2) and MgCl(2) enhanced the dextransucrase activity. A 22% higher dextransucrase activity was obtained by 4 mM CoCl(2). The dextransucrase activity was lost by 50% at 1 mM EDTA. Urea denatured the enzyme and caused 45%, 90% and 98% loss of activity in 30 min when treated with 1 M, 3 M, and 5 M urea concentrations, respectively. Amongst the stabilizers Tween 80, glycerol, PEG-8000, dextran (500 kDa) and glutaraldehyde, Tween 80 provided the maximum stability at 30°C. In the presence of Tween 80 the enzyme lost only 8% activity at 30°C in 20 h but, it lost 65% of activity with out any stabilizer. The enzyme lost 92% of activity with in 4 days at 30°C and lost only 25% of activity at −20°C after 14 days.